Degradation of crude oil in a co-culture system of Bacillus subtilis and Pseudomonas aeruginosa - Wu, Bo; Xiu, Jianlong; Yu, Li; Huang, Lixin; Yi, Lina; Ma, Yuandong (Frontiers in Microbiology, 2023)
The aim of this work was to research the potential of defined co-culture of Bacillus subtilis SL and Pseudomonas aeruginosa WJ-1 for biodegradation of crude oil. The residual oil, saturated and aromatic fraction in the samples were analyzed, after 7 days of incubation. The degradation ratio of crude oil was enhanced from 32.61% and 54.35% in individual culture to 63.05% by the defined co-culture of strains SL and WJ-1. GC-MS analysis showed that the degradation ratio of saturated and aromatic fraction in crude oil was improved as well. Furthermore, the study also found that the defined co-culture system represented relatively excellent performance in bacterial growth, cell surface hydrophobicity and emulsification activity. These results indicated that the combination of Bacillus subtilis and Pseudomonas aeruginosa effectively enhances the degradation and utilization of crude oil, which may provide a new idea for the improvement of bioremediation strategies.